Answer:
![-4 = x](https://img.qammunity.org/2020/formulas/mathematics/middle-school/9clctqe9sg1xq0ng5k9nlupo1d9eo1pecy.png)
And then we can replace the value of x on equation (1) or (2) and we got:
![y = 4* (-4) -4 = -20](https://img.qammunity.org/2020/formulas/mathematics/middle-school/6tw6wt9man42jo6tdj3h0lhxddp2k4dfhc.png)
And then we have our solutuon x = -4, y = -20
Explanation:
For this case we have the following system of equations:
(1)
(2)
And we can solve this system of equation using the method of elimination for example or we can set equal both equation since both are equal to y, like this:
![4x-4 = 5x](https://img.qammunity.org/2020/formulas/mathematics/middle-school/jerasb1mv4q9nf7v2trq5qbiax8qjhx0eh.png)
Now w can subtract 4x from both sides and we got:
![-4 = x](https://img.qammunity.org/2020/formulas/mathematics/middle-school/9clctqe9sg1xq0ng5k9nlupo1d9eo1pecy.png)
And then we can replace the value of x on equation (1) or (2) and we got:
![y = 4* (-4) -4 = -20](https://img.qammunity.org/2020/formulas/mathematics/middle-school/6tw6wt9man42jo6tdj3h0lhxddp2k4dfhc.png)
And then we have our solutuon x = -4, y = -20